Sistem Pengendalian Internal Kas Pada PT XYZ - Alwiyatun Nisa'; Anita Handayani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The internal control system is important for companies to maintain company assets, accuracy and reliability of data, encourage efficiency, and encourage compliance with management policies. The cash control system also needs to be considered as an effort to monitor and supervise the company's cash activities. This research aims to evaluate and determine the implementation of the cash internal control system at PT XYZ. The type of research used is qualitative with a case study approach. The data sources used in this study are primary data and secondary data. The data collection techniques in this research used interviews and documentation. The determination of informants was carried out using the snowball sampling method and the data analysis used was the Miles and Huberman model, and to test the validity of the data using triangulation techniques. The results of the research obtained data based on 4 (four) elements of the internal control system show that the existing organizational structure at PT XYZ is appropriate, then in document authorization there are documents that do not have the signature of the finance director so that it is lacking in authorizing company documents, company activities have reconciliations that are carried out regularly, and in the recruitment process there are several criteria required. So it can be concluded that PT XYZ has been said to be quite good in internal cash control so that the objectives of implementing control are achieved quite well.